1997
DOI: 10.1172/jci119373
|View full text |Cite
|
Sign up to set email alerts
|

Experimental expression in mice and spontaneous expression in human SLE of polyomavirus T-antigen. A molecular basis for induction of antibodies to DNA and eukaryotic transcription factors.

Abstract: We have previously demonstrated that experimental expression of the polyomavirus transcription factor T-antigen has the potential to induce anti-DNA antibodies in mice. Two sets of independent evidences are presented here that demonstrate a biological relevance for this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
151
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 45 publications
7
151
1
Order By: Relevance
“…Direct conjugation of Ag to ODN might unveil unexpected immunogenic aspects of DNA; it has been reported that DNA complexed to proteins or peptides induces the production of lupus-like anti-dsDNA Abs (45)(46)(47), whereas immunization with the DNAprotein complex was reported to attenuate murine lupus despite the induction of pathogenic Abs (48). As discussed above, the reasons for the possible deteriorating effects of autoimmune diseases by CpG-protein conjugates need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Direct conjugation of Ag to ODN might unveil unexpected immunogenic aspects of DNA; it has been reported that DNA complexed to proteins or peptides induces the production of lupus-like anti-dsDNA Abs (45)(46)(47), whereas immunization with the DNAprotein complex was reported to attenuate murine lupus despite the induction of pathogenic Abs (48). As discussed above, the reasons for the possible deteriorating effects of autoimmune diseases by CpG-protein conjugates need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Serum antibodies against dsDNA were detected and titrated by ELISA exactly as described previously (15,36). An anti-dsDNA mAb was included in each ELISA for intraassay validation (15,36).…”
Section: Methodsmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was performed to detect antibodies to nucleosomes, H1, dsDNA, DNase I, type IV collagen, heparan sulfate, and ␣-actinin, as described previously (27)(28)(29)(30). Essentially, microtiter plates (MaxiSorp; Nunc, Copenhagen, Denmark) were coated with nucleosomes (10 g/ml as DNA), dsDNA (10 g/ml), H1 (2 g/ml), heparan sulfate (10 g/ml), ␣-actinin (5 g/ml), DNase I (5 g/ml), and type IV collagen (5 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…All mAb, serum antibodies, and antibodies eluted from kidneys were diluted 2-fold in PBS-0.02% Tween 20. Relevant control antibodies were included in each ELISA for intraassay validation of results (22,29). The Crithidia luciliae immunofluorescence test (CLIFT) was performed to detect anti-dsDNA antibodies, as previously described (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation